THE CONTRIBUTION OF THE TOURISM SECTOR TO THE NEUTRALIZATION OF THE EXTERNAL IMBALANCE IN THE WESTERN BALKAN COUNTRIES - Čakajac, Božidar (The Business of Tourism, 2023)
Apart from the contribution to economic growth and development of the national economy, the tourism sector can represent an important factor in reducing the balance of payments imbalance. Thanks to the higher export compared to the import of tourist services, conditions are created for realizing a surplus in the exchange of tourist services, which can be a significant source of financing the current account deficit. This can be particularly important for the countries of the Western Balkans, since they are characterized by a balance of payments imbalance, but at the same time they have significant tourism potential that can be further valorized in order to reduce the current account deficit and mitigate the problem of external imbalance. Bearing the above in mind, the paper tries to quantify the contribution of the tourism sector in financing the current account deficit of the countries of the Western Balkans in the 2007-2022. period. The results of the research suggest that the importance of the tourism sector, as a factor in financing the balance of payments imbalance, varies significantly among the analyzed economies, with a positive contribution of the tourism sector in neutralizing the current account deficit recorded in all observed countries. Apart from the above, the research tries to show that there is a significant potential not only for the development of tourism potential in the countries of the Western Balkans, but also for its significant contribution in reducing the balance of payments imbalance as one of the key development limitations of the observed economies.
Keywords: tourism; current account; external imbalance; Western Balkan